The Effect of Satisfaction, Perceived Value, Image, and Perceived Sacrifice on Public Healthcare Service Institution’s Patient Loyalty - Medi Yarmen (Intelektual Pustaka Media Utama, 2017)
This research aims to investigate the simultaneous effect of satisfaction, perceived value, image, and perceived sacrifice on patient loyalty. This study is believed to be the first to develop and test patient loyalty model that includes satisfaction, perceived value, image, and perceived sacrifice. Quantitative research methodology was employed. We performed survey to collect the empirical data. The respondents are 162 patients of two health care service institutions in Bogor and Bekasi, Indonesia. The conceptual model and proposed hypotheses were examined using multiple regressions analysis. The findings showed that image has positive impact on patient loyalty. However, this research also found that satisfaction, perceived value, and perceived sacrifice do not have significant impact on patient loyalty. Thus, the management of public healthcare service institution should consider and manage the image of the institution proactively.